Batman [videorecording (DVD)] - Nicholson, Jack; Keaton, Michael, 1951-; Basinger, Kim, 1953- (Warner Bros. Entertainment, 2007)
A millionaire's son witnesses his parents' murder and grows up fighting the emotional trauma of that fateful night. To compensate, he develops a dual personality. During the day he's a playboy philanthropist, but at night, he becomes the dark persona Batman, a masked crusader for justice. While fighting crime in Gotham, he eventually has to face an arch-criminal known as The Joker.